2019
DOI: 10.1101/563049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A biophysical model of Epithelial-Mesenchymal Transition uncovers the frequency and size distribution of Circulating Tumor Cell clusters across cancer types

Abstract: The gain of cellular motility via the epithelial-mesenchymal transition (EMT) is considered crucial in the metastatic cascade. Cells undergoing EMT to varying extents are launched into the bloodstream as single circulating tumor cells (CTCs) or multi-cellular clusters. The frequency and size distributions of these multicellular clusters has been recently measured, but the underlying mechanisms enabling these different modes of migration remain poorly understood. We present a biophysical model that couples the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…According to this reduced physical model, a tumor can undergo a transition from primarily single cell-based invasion to collective invasion. Strikingly, this theoretical framework reproduces multiple CTC cluster size distributions measured in patients and mouse models across cancer types, hence suggesting the existence of a unifying set of principles governing cancer cell migration [130].…”
Section: An Alternative Mechanism -That Ctc Clusters Can Be Formed Vi...mentioning
confidence: 61%
See 1 more Smart Citation
“…According to this reduced physical model, a tumor can undergo a transition from primarily single cell-based invasion to collective invasion. Strikingly, this theoretical framework reproduces multiple CTC cluster size distributions measured in patients and mouse models across cancer types, hence suggesting the existence of a unifying set of principles governing cancer cell migration [130].…”
Section: An Alternative Mechanism -That Ctc Clusters Can Be Formed Vi...mentioning
confidence: 61%
“…To model the migration of CTC clusters, Bocci et al proposed a simple biophysical model where cancer cells can undergo a partial EMT that allows both single-cell and clustered-cell migration, or a complete EMT that only allows single-cell migration [130]. According to this reduced physical model, a tumor can undergo a transition from primarily single cell-based invasion to collective invasion.…”
Section: An Alternative Mechanism -That Ctc Clusters Can Be Formed Vi...mentioning
confidence: 99%
“…They underwent partial EMT and acquired some mesenchymal features, while maintaining epithelial characteristics (i.e., EMT state) ( Williams, Gao, Redfern and Thompson, 2019 ). This hybrid state allows CTC to revert to the epithelial state (i.e., mesenchymal-epithelial transition) ( Bocci, Jolly and Onuchic, 2019 ). Although it has been reported that platelets increase mesenchymal features in cancer cell lines ( Labelle et al, 2011a ), we did not observe this effect in our CTC lines.…”
Section: Discussionmentioning
confidence: 99%
“…CTCs can migrate either as individual cells or in units of two or more cell clusters [169]. Various spatiotemporal patterns in EMT phenotypes may influence frequencies and size distributions of CTC clusters [171], which are considered the primary harbingers of metastasis [172]; thus, an understanding of their characteristics, such as size distribution, frequency, ability to traverse capillaries [173], and molecular profiles of their tumor and/or stromal cell populations [174], holds promise in highlighting new therapeutic vulnerabilities. Connecting these traits of CTC clusters to spatiotemporal dynamics of EMT in a primary tumor has yet to be undertaken comprehensively.…”
Section: Spatiotemporal Dynamics Of Emt and Cscsmentioning
confidence: 99%